Foreign Policy Analysis of the Republic of Korea in the Context of Sino-American Strategic Competition (2017-2024) - Ruiz, Rocío (2025)
The bilateral relationship between the People’s Republic of China (PRC) and the United States of America (USA) has been marked not only by cooperation, but primarily by antagonism. This relation, characterized as a “strategic competition,” has reshaped the contemporary international environment and has led numerous countries, such as the Republic of Korea (ROK), to adapt their foreign policy. In this context, this research applies an ad hoc foreign policy analysis (FPA) model to analyze the ROK’s international behavior between 2017 and 2024.Based on a qualitative approach, findings show that the ROK’s foreign policy is shaped by both internal determinants, such as its objectives, and external ones, particularly the international structure. Its economic and security dependence on the USA, and its economic ties and geographic proximity to the PRC and the Democratic People’s Republic of Korea, have led the ROK to consolidate a dual hedging strategy, preserving its autonomy and avoiding full alignment. This ambiguity has been key for the ROK to assume a more active role—especially through its Indo-Pacific strategy—and to strengthen its regional and global influence as a “Global Pivotal State.”